Fake News? Quantifying the Prevalence of Misinformation Related to Scoliosis on the TikTok Social Media Platform - Banahene Glover, BS; Anne-Marie Datcu, BS; Macy Meyer, BS; Emily Lachmann, BS; Amy McIntosh, MD; Megan Johnson, MD; Jaysson T. Brooks, MD (Journal of the Pediatric Orthopaedic Society of North America)
Background: The lack of presence by spine deformity surgeons on TikTok, in addition to the platform’s unregulated nature, raises concerns about the potential spread of misinformation regarding pediatric orthopaedic conditions. The purpose of this study is to assess the prevalence of scoliosis misinformation on TikTok with a specific focus on what types of scoliosis content contain the most misinformation and which content creators produce the most videos containing this misinformation. Methods: A comprehensive search was conducted on TikTok using the following hashtags: #scoliosis, #scoliosischiropractor, #scoliosisbrace, #scoliosissurgery. A total of 239 videos were reviewed over a 7-day period by three reviewers. Videos were categorized based on tone, content type, and healthcare provider involvement. Three pediatric spine surgeons reviewed flagged videos for misinformation related to scoliosis. Quality assessment was performed using the Global Quality Scale (GQS) and the DISCERN scoring system, with a score of 5 denoting the highest quality. Results: TikTok videos related to scoliosis received on average 2.4 million views. Most TikTok scoliosis videos, 72.8% (n = 174), were created by patients sharing their experiences. When measuring video content quality, videos by physicians scored significantly higher with mean DISCERN and GQS scores of 3.3 ± 0.5 and 3.7 ± 0.4, respectively, compared to chiropractors with mean DISCERN and GQS scores of 2.3 ± 0.6 and 2.5 ± 0.5 (P < .0001). Forty-four percent (n = 24) of videos offering scoliosis advice were found to contain misinformation. The majority of these misinformation videos were produced by chiropractors (46%, n = 11) compared to physicians (12.5%, n = 3), although this was not statistically significant. Videos containing misinformation related to scoliosis garnered 2.2 ± 5.2 million views versus videos that did not contain misinformation, which received 1.6 ± 5.1 million views (P = .7). Conclusions: Chiropractors are the most frequent healthcare providers offering scoliosis advice on TikTok. The quality of information presented by chiropractors was found to be significantly lower than that of physicians. Spine deformity surgeons should be aware of TikTok's market dominance and provide high-quality information to counter the misinformation currently present on the platform related to scoliosis. Key Concepts: (1) The limited presence of spine deformity surgeons on TikTok contributes to the spread of scoliosis misinformation. (2) Patient-generated TikTok videos dominate scoliosis content but frequently lack evidence-based guidance. (3) Chiropractors are the most common healthcare providers posting scoliosis advice, although their content often scores lower in reliability. (4) Physician-led videos generally demonstrate higher DISCERN and GQS scores, emphasizing the value of expert-produced content. (5) Greater involvement of spine deformity surgeons on TikTok could reduce misinformation and improve patient education. Level of Evidence: Level IV study